Melange: Space Folding for Visual Exploration - Elmqvist, Niklas; Riche, Yann; Henry Riche, Nathalie (IEEE Transactions on Visualization and Computer Graphics, 2010)
Navigating in large geometric spaces—such as maps, social networks, or long documents—typically require a sequence of pan and zoom actions. However, this strategy is often ineffective and cumbersome, especially when trying to study and compare several distant objects. We propose a new distortion technique that folds the intervening space to guarantee visibility of multiple focus regions. The folds themselves show contextual information and support unfolding and paging interactions. We conducted a study comparing the space-folding technique to existing approaches, and found that participants performed significantly better with the new technique. We also describe how to implement this distortion technique, and give an in-depth case study on how to apply it to the visualization of large-scale 1D time-series data.